Electrophysiological correlates of skill-specific modulations of cognitive control in badminton players - Sun, J.; Tu, K. C.; Wang, C. H.; Tsai, C. L. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Recently there have been increasing researches suggest that sports training involving cognitive skills (i.e., open-skilled sports) may be associated with enhanced cognitions. However, sports training has been associated with enhanced aerobic fitness, which is also beneficial for cognitive functions. Thus, it is unclear whether the skill-specific effect of sports training on cognitions can still be observed after accounting for the fitness effect. Accordingly, this study compared neurocognitive performance with those of athletes in other sports requiring less complex cognitive skills (i.e., track and field) to further address this issue. Method: We examined the differences in behavioural and event-related potential (ERP) measures during a flanker task involving different levels of cognitive control between badminton players (n = 16; aged 20.68 ± 1.9 years; VO2max = 55.69 ± 0.9 mL/kg·min) and fitness-matched athletic controls (n = 16; aged 20.94 ± 1.1 years; VO2max = 55.20 ± 2.1 mL/kg·min). Result: Behaviour data showed that badminton players responded faster than non-players selectively in the condition involving higher level of cognitive control (i.e., response conflict in the incongruent condition). In addition, the ERP data showed that, as compared to the athletic controls, badminton players exhibited smaller N2 amplitudes but greater P3 amplitudes at electrodes around fronto-central areas (i.e., Fz, FCz, CPz). Discussion: These combined analysis of behaviour and ERP data suggested that long-term participation in a sport requiring intense cognitive skills (i.e., badminton) may be related to a reduction in taskrelevant response conflict, with a concomitant increased top-down attentional control during task execution, thus better task performance. Based on these findings, we conclude that the sport-skill-specific changes in cognitive function might be independent of aerobic fitness, further supporting the claim that mental training in sports may be a medium for cognitive enhancement.